THE USE OF GAMIFICATION TECHNOLOGY IN THE DEVELOPMENT OF SCIENCE MATERIAL TEACHING MATERIALS IN PRIMARY SCHOOL - Qurotul A’yun, Dya; Mardiyana, Isna Ida (FORPIM PTKIS ZONA TAPAL KUDA, 2024)
Global advances in technology have influenced all aspect of life in the fields of economics, politics, culture, and even in the world of education. Teachers need to understand how their students learn and find the best way to utilize technological advances. Gamification is one of the technological developments that can be used in learning. The learning process of course cannot be separated from the use of teaching materials. The aim of this research is to describe the validity and attractiveness of using gamification technology. This research is development research eith a 4-D model developed by Thiagarajan. Based on the research results, to determine the validity of e-module teaching materials by using validation sheets by material experts dan teaching material experts. Based on the material expert validation questionnaire, followed by data processing and analysis using criteria, a score of 97,5% was obtained with very valid criteria. Meanwhile, the validation questionnaire by teaching materials experts and continued with data processing obtained a score of 88,46% with very valid criteria. To find out the attractiveness of e-module teaching materials by using 1 questionnaire for students in large group trials, scores of 84,76% and 83,55% werw obtained, both of which are very attractive criteria. The conclusion of this research is that the development of gamification- based teaching materials is very valid and very interesting.